Short Communication: Growth response and dependency of endangered nedun tree species (Pericopsis mooniana) affected by indigenous Arbuscular Mycorrhizal Fungi inoculation - HUSNA HUSNA; FAISAL DANU TUHETERU; ENDAH WIGATI (Nusantara Bioscience, 2017)
Husna, Tuheteru FD, Wigati E. 2017. Short Communication: Growth response and dependency of endangered nedun tree species (Pericopsis mooniana) affected by indigenous Arbuscular Mycorrhizal Fungi inoculation. Nusantara Bioscience 9: 57-61. Arbuscular mycorrhizal fungi (AMF) were isolated from the rhizosphere of local nedun tree or kayu kuku (Pericopsis mooniana (Thw.) Thw.) and based on the results of previous studies which showed that inoculation with AMF mix enhanced growth and nutrient uptake of seedlings P. mooniana on ultisol and serpentine soil media. Thus study aimed to determine the effectiveness of indigenous AMF on the growth and dependence of P. mooniana. P. mooniana seedlings were grown on ultisol soil medium and inoculated with and without AMF (Clareodeglomus etunicatum, Glomus sp. (HA), Glomus sp. (KDI)) and mixed (C. etunicatum, Glomus sp. (HA), Glomus sp. (KDI) for 12 weeks under greenhouse conditions. The results showed that inoculation with Glomus sp. (HA) significantly increased plant height, stem diameter, number of leaves, dry weight (roots, shoots, total), nodulation, root length and leaf length. It was better than results on control of P. mooniana seedling but it was not significantly different from other types of AMF, except on Glomus sp. (HA) on plant height. The width of the leaf and shoot-root ratio was not influenced by the AMF. P. mooniana has a high dependency (<75%) with mycorrhizal dependency (MD) value ranging from 54-68%. Glomus sp. (HA) and other types of AMF have potential to be developed to support the conservation of P. mooniana.